J.K. Lasser's small business taxes 2015 : your complete guide to a better bottom line - Weltman, Barbara, 1950- (J.K. Lasser--practical guides for all your financial needs., 2015)
Eliminate confusion, maximize deductions, reduce payments, and conquer your small business taxes with ease In J.K. Lasser's Small Business Taxes 2015, the most trusted name in tax guidance helps small business owners maximize their bottom line. Fully updated for 2014 tax returns and 2015 tax planning, this detailed guide provides concise, plain-English explanations of tax laws tailored to business owners who are experts in their field'not in taxes. A complete listing of available business expense deductions includes comprehensive information on dollar limits and record-keeping requirements, allowing business owners to quickly recognize the deductions for which they qualify and make tax-savvy business decisions year round. Sample forms and checklists allow you to organize your preparation, and clear instruction on tax form navigation helps you get it right the first time. Small business owners have a full plate. Indeed, just keeping the business going is a more than full-time job. But when tax time rolls around, you still need to file'correctly, on time, and without making errors or leaving money on the table. Small Business Taxes 2015 simplifies the process, breaking down tax laws and the filing process. You'll get expert insight on every step of the process, from organizing paperwork to sending the check, including clear guidance on how to: -Create a year-long record-keeping system that will streamline the filing process -Clarify income and losses and deal with operational income and losses, capital gains, and property sales -Discover the latest tax credits and deductions that may apply to your business -Tailor a tax strategy to your business's size, maturity, and growth potential Frustration-free filing is not a myth. With the proper planning and understanding, you can save your business a significant amount of money, without wading through volumes of tax legalese. J.K. Lasser's Small Business Taxes 2015 provides the facts, strategies, and up to date information you need to get it done right, and get back to work.